Implementation of Benson Relaxation Technique to Reduce Acute Pain Post-Cesarean Section - Nur Khoerotun Nisa; Siti Haniyah (LPPM Universitas Harapan Bangsa, 2024)
Childbirth is the stage of expelling the products of conception through the birth canal with or without assistance. The birth process is classified into 2 ways, namely normal delivery and caesarean section (Sectio Caesarea). Caesarean section can have a negative impact, namely physically causing pain in the stomach during surgery which has a higher pain level, namely 27% compared to the normal birth stage which has a lower pain level, namely 9%. Pain can be prevented with non-pharmacological therapy, one of which is the Benson relaxation technique. This study aims to determine the effectiveness of the Benson relaxation technique in reducing pain in mothers after cesarean section. This research is qualitative research with a case study method using a nursing process approach. The subjects used were post-cesarean section patients with acute pain problems at Kardinah Hospital, Tegal City. The research instrument used was the maternity nursing care format. Research data collection techniques are observation, interviews, physical examination and documentation studies. The instrument used to measure pain is the Numeric Ratting Scale (NRS), pain measurements are carried out before and after the Benson relaxation technique. The results of applying the Benson relaxation technique to mothers after cesarean section showed that the patient experienced a decrease in the level of pain from the first day of treatment to the third day of treatment, namely from a scale of 7 to a scale of 3. These results show that the Benson relaxation technique was able to minimize the scale of pain in mothers after cesarean section